Navigate : workbook without key. A2, Elementary - Tabor, Carol (Oxford University Press, 2015)
Navigate is a brand new, six-level General English course tailored exclusively to adults. The course takes an innovative approach to reading and listening based on academic research as to how adults best learn languages. It teaches reading and listening from the bottom up, giving learners the skills they need to understand the next text they will read and hear, not just the one they are reading or hearing now. The content has been extensively piloted and reviewed in ELT classrooms across the world, giving teachers the confidence that it really works.